ABC ANALYSIS, FORECASTING AND ECONOMIC ORDER QUANTITY (EOQ) IMPLEMENTATION TO IMPROVE SMOOTH OPERATION PROCESS - Thukas Shilul Imarah; Roni Jaelani (Dinasti Publisher, 2020)
The study aims to test the effectiveness of the implementation of several inventory control methods to improve the smooth operation in a trading company of industrial equipements components that have difficulty in maintaining inventory data accuracy, inventory shortages and in other hand excess unrequired inventory. The research data used is taken from the ERP report data and manual reports created by the perpetrators of the operational activities of the Inventory Control for the period 2016 - 2018. The sampling method used is purposive sampling of the product sales data in years 2016 – 2018 as much as 2498 Stock Keeping Unit (SKU) which is then processed using the method of ABC analysis and FSN (Fast Moving, Slow Moving and None Moving) analysis to get 10 SKUs that belongs to the category A and F (Fast Moving) group as a sample of research. The research method uses the Quantitative method with the use of ABC analysis, Forecasting and Economic Order Quantity. The results shows that the implementation of ABC analysis effectively reduced the workload of periodic counting and is able to improve data accuracy to be higher level. The exponential smoothing forecast method shows the least gap to the actual value and EOQ effectively optimizes ordering and holding costs and reduces the risk of failure in Inventory Control and positively affects the smoothness of the operation process.